Lung Fibroblasts from Chronic Obstructive Pulmonary Disease Subjects Have a Deficient Gene Expression Response to Cigarette Smoke Extract Compared to Healthy - Garcia-Ryde, Martin; van der Burg, Nicole; Larsson, Carin E; Larsson-Callerfelt, Anna-Karin; Westergren-Thorsson, Gunilla; Bjermer, Leif; Tufvesson, Ellen (International journal of chronic obstructive pulmonary disease, 2023)
Cigarette smoking is the most common cause of chronic obstructive pulmonary disease (COPD) but more mechanistic studies are needed. Cigarette smoke extract (CSE) can elicit a strong response in many COPD-related cell types, but no studies have been performed in lung fibroblasts. Therefore, we aimed to investigate the effect of CSE on gene expression in lung fibroblasts from healthy and COPD subjects. Primary lung fibroblasts, derived from six healthy and six COPD subjects (all current or ex-smokers), were either unstimulated (baseline) or stimulated with 30% CSE for 4 h prior to RNA isolation. The mRNA expression levels were measured using the NanoString nCounter Human Fibrosis V2 panel (760 genes). Pathway enrichment was assessed for unique gene ontology terms of healthy and COPD. At baseline, a difference in the expression of 17 genes was found in healthy and COPD subjects. Differential expression of genes after CSE stimulation resulted in significantly less changes in COPD lung fibroblasts (70 genes) than in healthy (207 genes), with 51 genes changed in both. COPD maintained low NOTCH signaling throughout and upregulated JUN >80%, indicating an increase in apoptosis. Healthy downregulated the Mitogen-activated protein kinase (MAPK) signaling cascade, including a ≥50% reduction in FGF2, CRK, TGFBR1 and MEF2A. Healthy also downregulated KAT6A and genes related to cell proliferation, all together indicating possible cell senescence signaling. Overall, COPD lung fibroblasts responded to CSE stimulation with a very different and deficient expression profile compared to healthy. Highlighting that stimulated healthy cells are not an appropriate substitute for COPD cells which is important when investigating the mechanisms of COPD.